Respuesta :

Step-by-step explanation:

Hey there!

Given equation is; 6x + y= 6.

6x + y -6=0........……(i)

Slope (m1) = (-coefficient of X)/(coefficient. of y)

Slope (m1) = (-6)/(1)

Therefore, slope of the equation is -6.

As per the condition of parallel lines, slope of 1st equation is equal to 2nd equation.

Therefore, m1=m2= -6

The another straight line passes through the point (2,-5). So to find the equation, use one-point formula.

(i.e (y-y1) = m2(x-x1)).

So, the equation is;

(y+5) = m2(x-2)

Now, we know that m1=m2= -6. Let's keep its value on it.

y+5 = -6(x-2)

Or, y+5 = -6x +12

Or, 6x+ y -7 = 0

Therefore, the equation which is parallel to 6x + y= 6 equation and passes through the point (2,-5) is 6x+y-7=0.

Hope it helps...